The fate of organic carbon burial in the river-dominated East China Sea: Evidence from sediment geochemical records of the last 70 years - Sun, Xueshi; Fan, Dejiang; Liu, Ming; Liao, Huijie; Tian, Yuan (Organic geochemistry, 2020)
•Human induced-river damming and cultivated land changes controlled the export of terrestrial organic carbon to the ocean.•Marine productivity increased due to increasing nutrient supply, following the use of N and P fertilizers.•Organic carbon burial fluxes were regulated by changes in sedimentation accumulation rates and organic carbon content.•The construction of the Three Gorges Dam (TGD) significantly impacted the burial and preservation of organic carbon. The accumulation of organic carbon (OC) in the sediments of river-dominated continental margins plays a critical role in the global carbon budget and is subject to human modification. However, the relationships between human activities in drainage basins and carbon burial in modern sediments are still poorly understood. Here, a well preserved sediment core from a mud zone in the East China Sea (ECS) was analyzed for isotopes (δ13Corg and δ15N), radioisotopes (210Pb and 137Cs), bulk organic carbon and nitrogen, sediment grain size, major elements, trace metals and chemical properties (pH and Eh), in order to reveal the fate of the OC buried in the studied shelf over the last 70 years. The results showed that the input of terrestrial organic matter (TOM) from the Yangtze River into the ECS declined by 15% between 1980 and 2005, in concomitance with decreasing terrestrial-derived Ca and Zr. These changes were mainly due to alterations in the sediment load and cultivated land, induced by river damming and soil conservation practices. The amount of marine organic matter (MOM) was strongly and positively correlated with chlorophyll a concentrations and the loads of dissolved inorganic nitrogen and phosphate. The discharge of riverine nutrients from artificial fertilizers seems to be one of the key factors influencing marine productivity. OC burial fluxes varied between 33.8 and 54.7 g C m−2 yr−1 and were primarily related to changes in the mass accumulation rates (MARs) and OC%. Notably, due to the construction of the Three Gorges Dam (TGD) in 2003, the input of eroded material from the downstream and subaqueous delta of the Yangtze River increased, profoundly altering the local hydrodynamics and sedimentary redox levels. These changes may, in turn, accelerate the degradation of sedimentary OC, preventing carbon deposition and preservation.